3D Printing of Free Standing Liquid Metal Microstructures. (4th July 2013) - Ladd, Collin; So, Ju‐Hee; Muth, John; Dickey, Michael D.
<x xml:space="preserve">Abstract</x> This paper describes a method to direct‐write 3D liquid metal microcomponents at room temperature. The thin oxide layer on the surface of the metal allows the formation of mechanically stable structures strong enough to stand against gravity and the large surface tension of the liquid. The method is capable of printing wires, arrays of spheres, arches, and interconnects. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>